Human rights v. Insufficient climate action: The Urgenda case. Issue 2 (June 2019) - Leijten, Ingrid
Climate change is a human rights issue, but what exactly can courts require States to do in this regard? This contribution discusses the Dutch Urgenda case, in which the Court of Appeals recently found a violation of Articles 2 (right to life) and 8 (right to respect for private and family life) of the European Convention on Human Rights and ordered the State to reduce greenhouse gas emissions by 25% by 2020. Looking at the case law of the European Court of Human Rights on environmental issues, as well as the nature of positive obligations, it appears that Urgenda involves a more abstract situation and a more precise positive obligation than is usually the case in human rights adjudication. Because ex post facto complaints are no solution, and in light of the growing number of Urgenda- like cases pending before (international) courts, efforts need to be made to ensure that human rights `fit' climate change cases and courts can provide effective protection in this regard.